Marketing Strategy Analysis To Increase Virgin Coconut Oil (VCO) Sales At UD. Delaria - Gea, Melianus; Zebua, Serniati; Harefa, Idarni; Laia, Otanius (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This research aims to analyze the marketing strategies implemented by UD. Delaria in marketing Virgin Coconut Oil (VCO) products, evaluating internal and external factors that affect the effectiveness of the strategy, and formulating strategic recommendations to increase sales. The research method used is qualitative with data collection through interviews, observations, and document analysis. The research method used is qualitative with data collection through interviews, observations, and document analysis. The results of the study show that UD. Delaria combines direct selling strategies with digital marketing (internet marketing) to reach a wide range of consumers and retain existing customers. The most influential internal factor is the superior quality of VCO products, while external factors include consumer behavior that is increasingly concerned about health but price sensitive, as well as fierce market competition. The proposed strategies include strengthening targeted digital marketing, consumer education on the benefits of VCO, creative promotion, packaging innovation, and product variant development. This approach is expected to be able to expand market reach, increase brand awareness, build consumer loyalty, and maintain sales stability in a sustainable manner.